Metabolomic Profiling and Anti-Helicobacter pylori Activity of Caulerpa lentillifera (Sea Grape) Extract - Chananchida Thacharoen; Thisirak Inkaewwong; Watthanachai Jumpathong; Pornchai Kaewsapsak; Thiravat Rattanapot; Tippapha Pisithkul (Marine Drugs, 2025)
Helicobacter pylori is a gastric pathogen implicated in peptic ulcer disease and gastric cancer. The increasing prevalence of antibiotic-resistant strains underscores the urgent need for alternative therapeutic strategies. In this study, we investigated the chemical composition and antibacterial activity of an aqueous extract from Caulerpa lentillifera (sea grape), a farm-cultivated edible green seaweed collected from Krabi Province, Thailand. Ultra-high-performance liquid chromatography–tandem mass spectrometry (UHPLC-MS/MS) revealed that the extract was enriched in bioactive nucleosides and phenolic compounds. In vitro assays demonstrated dose-dependent inhibition of H. pylori growth following exposure to sea grape extract. Furthermore, untargeted intracellular metabolomic profiling of H. pylori cells treated with the extract uncovered significant perturbations in central carbon and nitrogen metabolism, including pathways associated with the tricarboxylic acid (TCA) cycle, one-carbon metabolism, and alanine, aspartate, and glutamate metabolism. Pyrimidine biosynthesis was selectively upregulated, indicating a potential stress-induced shift toward nucleotide salvage and DNA repair. Of particular note, succinate levels were markedly reduced despite accumulation of other TCA intermediates, suggesting disruption of electron transport-linked respiration. These findings suggest that bioactive metabolites from C. lentillifera impair essential metabolic processes in H. pylori, highlighting its potential as a natural source of antimicrobial agents targeting bacterial physiology.